Taxonomic study on the genus Pselaphodes Westwood (Coleoptera, Staphylinidae, Pselaphinae) from China. Part III - Yin, Zi-Wei; Li, Li-Zhen; Gu, Fu-Kang (Zootaxa, 2012)
Three new species of Pselaphodes are described and illustrated from Guangxi, South China: P. dayaoensis Yin & Li sp.n., P. hui Yin & Li sp. n. and P. maoershanus Yin & Li sp. n. New distributional data is given for P. condylus Yin, Li &Zhao, 2011 and P. tianmuensis Yin, Li & Zhao, 2010. An updated key is provided to include these additions. The genus presently contains 27 species in China.